EU law and the detainability of asylum-seekers - Costello, Cathryn; Mouzourakis, Minos (Refugee Survey Quarterly, 2016)
This article examines detention of asylum-seekers, more specifically how European Union law simultaneously constructs the asylum-seeker as a detainable subject, while also limiting States' powers of detention. The power to detain is limited by international refugee and human rights law, but European Union law sets more stringent standards. While international refugee law regards the asylum-seeker as a presumptive refugee, European Union law seems to take a different view. Nowadays, the legal and physical rite of passage from irregular migrant to asylum-seeker to refugee defines the predicament of refugees who seek protection in the European Union. Asylum-seekers are vulnerable to detention as irregular entrants, when they are in transit in search of effective protection, and if they become deportable under the Dublin System. Coercive forms of detention are, too glibly in our view, assumed to be permitted to ensure they cooperate with identification and registration processes. The article aims to problematise this detainability of asylum-seekers, examining in particular how their increasing deportability and transferability may increase their detainability. Drawing on empirical examples from the treatment of refugees arriving in the European Union in 2015, it suggests that the Union's legal limits on detention need further implementation and institutionalisation.
CRIS-Team Scopus Importer:2023-03-21
Keywords: Asylum-seekers; Detainability; Detention; European union